Compilation of Research Outputs Volume 1 - Carpio,Geraldine Therese S. De Villa, Katriela Marie S. Manabat,Alexa Marie C. Pardilla, Ma. Denise Andrea F. and Tan, Nicole Allison M. et.al. 4 0 16; 5 (2016)
THE RELATIONSHIP BETWEEN TEACHER'S TEMPERAMENT AND SELECTED STUDENTS ACHIEVEMENT MOTIVATION WITH STUDENTS ACADEMIC PERFORMANCE IN COLLEGE ALGEBRA --- ABSTRACT: The purpose of this quantitative - qualitative study is to examine the temperament traits (nervous, depressive, active, expressive, sympathetic, subjective, dominant, hostile, and self-disciplined) of a College Algebra professor and the achievement motivation of the 2nd Year BS Psychology students from Pamantasan ng Lungsod ng Maynila (n=83, age range = 15 - 17), as they relate to the latter's academic performance on the subject. Moreover, this study answers questions regarding the demographic profile of the respondents, the contributing factors that justify the results gathered, and the learning recommended to teachers and students. The students rated their own achievement motivation using a self-report questionnaire and also rated their teacher's temperament traits by the use of a criss-cross test. Correlational analyses indicated that of the nine temperament traits only the sympathetic trait had a significant negative relationship (r=-.389, p<.001) with the students academic performance. This indicates that the professor's display of concern and compassion to the students typically influenced the decline of their academic performance. Findings point to the importance of having professors who are not too lenient and having a math enrichment program to promote learning and enjoyment in the subject.;FIGURATIVE ASSOCIATION: AN APPROACH TO BETTER AND FASTER LEARNING FOR SENIOR HIGH STUDENTS IN CALOOCAN----ABSTRACT: This paper investigated the effectiveness of mnemonic techniques and the most effective technique in recalling and memorizing of words among the Grade 11 Senior High School students of Young Achievers School of Caloocan A.Y 2016-2017. A total of 186 respondents were chosen to participate in the study. The participants were divided into two groups; control and experimental. The control group served as the independent variable and the experimental group as the dependent variable. Both groups were provided with a pre-test and post-test except that the experimental group undergone three post-test, one per technique used. 50 words were given to the participants to memorize within ten minutes. Three mnemonic techniques were provided by the researchers to the experimental group namely acronym, putting a rhythm and making a song. The results yielded that there is a significant difference between the experimental and control group. Also, there is a significant difference among the 3 techniques that was used. The scores of the experimental group showed that among the 3 techniques given, outing-a-rhythm mnemonic technique yielded the highest mean score, making it the most effective technique.;THE RELATIONSHIP BETWEEN SMARTPHONE USAGE AND FAMILY INTERACTION AMONG SELECTED HIGH SCHOOL STUDENTS-----ABSTRACT: This study shows the relationship of smartphone usage to the interaction and relationship among selected high school students. A total of 100 Grade 9 students ages 13-16 studying at President Osmeña High School located at Tondo, Manila are the sample used. The result of the smartphone usage test developed by the researcher's shows that the respondents are not prevalent of smartphones. Based on the scores of family interaction and smartphone usage, it shows that the two variables have correlation but only have slight effect on each other. The researchers concluded that even though the interaction of the family is lessen due to the fact that they use their smartphone instead of talking to each other, it also strengthens the connection of the family because they can call or text each other when they are not together physically. The researchers proposed a learning program that recommends the students/teenagers and also with their parents to strengthen their ties to each other by having a leisure or family time that they can spend for a better and stronger bond with each other than merely using their smartphones alone.;THE EFFICACY OF MUSIC IN ELICITING EMOTIONS AMONG YOUNG ADOLESCENTS-----ABSTRACT: The purpose of this study is to identify the efficacy of music in the elicited emotions of young adolescents. Music has been used for thousands of years as a means of emotional expression because it has the power of stimulating strong emotions within individuals. People can express their emotions and feelings and can cope up with formidable circumstances with the aid of music. The respondents were chosen purposively, they were supposed to be enrolled at Victorino Mapa High School, currently on grade seven or grade eight, and aged eleven to fourteen years old, male or female. A quasi-experimental design was used in conducting the study. There were two groups utilized - control and experimental group. Both groups were asked to answer a 20-item questionnaire for pre-test. The experimental group was introduced to uplifting and dark music, while the control was not. After which, a post-test was administered to distinguish the elicited emotion. PANAS scale is the instrument used by the researchers. An independent sample t-test is the statistical method utilized in this particular study. Results showed that there is a significant difference between music and elicited emotions. This study presented that music; especially uplifting music affects the elicited emotions of young adolescents.
Figurative Association: an Approach to Better and Faster Learning for Senior High Students in Caloocan.;The Relationship Between Smartphone Usage and Family Interaction among Selected High School Students.;The Efficiency of Music in Eliciting Emotions among Young Adoloscents.;The Relationship between Teacher's Temperament and Selected Students Achievement Motivation with Students Academic Performance in College Algebra.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2